Gerrhonotus parvus Knight & Scudday, 1985 (Squamata: Anguidae): New range extension and clutch size in the state of Nuevo León, Mexico - Banda Leal, Javier; Lazcano Villarreal, David; Nevárez de los Reyes, Manuel; Barriga Vallejo, Carlos (2014)
We report a female specimen of Gerrhonotus parvus that represents a new record for the municipality of Santa Catarina, Nuevo León, Mexico. This species was known previously from only three localities in the state: the municipalitiy of Galeana; the type locality, Los Rayones, where only one specimen was registered; and San Isidro Canyon in Santiago, which previously was the northernmost locality and where the largest number of specimens have been observed and collected. This new record extends the range of the species 48.2 km northeast of the nearest known locality in Santiago. In addition, the specimen laid six eggs, which is the largest clucth documented so far. The type locality is located in a transition zone between pine forest (Pinus arizonica) and open gypsophilous scrub. However, the nature of the microhabitats at the other localities, including the northernmost one reported here, suggests that the species has a preference for dry limestone canyons.